PENANAMAN PENDIDIKAN KARAKTER PEDULI LINGKUNGAN BERBASIS KEPEMIMPINAN MENUJU SEKOLAH ADIWIYATA PADA SISWA SD MUHAMMADIYAH WIROBRAJAN 1 - Adelia Verlian Viscadevi; Melinda Salsabila; Titin Suderazatul Absah (LPPM Universitas Cipta Mandiri, 2024)
This research aims to explain the character education used to train environmental care skills towardsadiwiyata school for students at SD Muhammadiyah Wirobrajan 1. The research uses a qualitativeapproach with descriptive methods. The data obtained is based on observation. The data that researchersobtain is then described scientifically so that a conclusion is obtained on the research. The results of thisresearch indicate that the cultivation of environmentally caring character education is influenced byleadership factors which have a major influence on the success of developing environmentally caringcharacter. Implementation is through various planned activity programs. The programs implementedrange from making compost, planting vegetable plants, making posters and slogans, morning adviceand adiwiyata campaigns. Through the programs presented, students become more diligent and activelyinvolved in solving environmental problems. By instilling character education that cares about theenvironment towards Adiwiyata schools in students at SD Muhammadiyah Wirobrajan 1, it can helpfoster good habits in students caring for the environment.